EFEKTIVITAS PROGRAM PEMASARAN PARIWISATA OLEH DINAS PARIWISATA KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Fadjri, Adjie Muhammad (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to analyze the effectiveness of tourism marketing programs implemented by the Sumedang Regency Tourism, Culture, Youth and Sports Office. The method used is descriptive qualitative with a focus on the six dimensions of program effectiveness according to Gibson's theory, namely clarity of purpose, strategy, analysis, planning, infrastructure, and supervision and control. The results showed that the marketing program has shown an increase in tourist visits from year to year, but still faces several obstacles such as less than optimal digital promotion strategies, limited supporting facilities, and lack of collaboration between stakeholders. Efforts made to overcome obstacles include increasing policy socialization, efficient implementation time, strengthening support, and adjusting tasks between implementers. The conclusion of this study states that although the program has shown positive achievements, its effectiveness has not been optimal and requires strengthening in the aspects of coordination, digitalization of promotion, and development of destination supporting infrastructure. Recommendations are given so that tourism marketing programs can be more strategic, participatory, and sustainable in encouraging Sumedang as a leading destination in West Java.